Description of collective behaviour in football according to the level of competence in representative tasks from positional data: Systematic review - Nieto, S.; Castellano, J.; Echeazarra, I. (International Journal of Sports Science & Coaching, 2022)
The aim of this systematic review is to provide a base of knowledge from studies that have dealt with the description of collective behaviour in young footballers according to the level of competence associated to that age group, taking representative tasks from positional data as our starting point. Following the PRISMA statement a systematic revision was carried out on three meta-search engines (PubMed, Web of Science and SportDiscus). The following key words were used in the search: football, tactical behaviour, positional data and age-group, together with their equivalents. Of the 423 articles identified, 11 fulfilled the inclusion requirements. The main results suggest that: the variables made up of the joining of two points with a line (Width, Length and distance between dyads) and the collective area covered increase with age; however, the individual area tends to reduce. The increase in level of competence appears to require a greater functional variability in order to generate uncertainty and to counteract that of the opposing team. These results could allow trainers to identify on which tactical behaviour to focus intervention with the aim of fostering optimal development according the age.